Plant Growth-Promoting Rhizobacteria Eliminate the Effect of Drought Stress in Plants: A Review - Ahmad, Hafiz Muhammad; Fiaz, Sajid; Hafeez, Sumaira; Zahra, Sadaf; Shah, Adnan Noor; Gul, Bushra; Aziz, Omar; Mahmood-Ur-Rahman,; Fakhar, Ali; Rafique, Mazhar; Chen, Yinglong; Yang, Seung Hwan; et al. (Frontiers in Plant Science, 2022)
Plants evolve diverse mechanisms to eliminate the drastic effect of biotic and abiotic stresses. Drought is the most hazardous abiotic stress causing huge losses to crop yield worldwide. Osmotic stress decreases relative water and chlorophyll content and increases the accumulation of osmolytes, epicuticular wax content, antioxidant enzymatic activities, reactive oxygen species, secondary metabolites, membrane lipid peroxidation, and abscisic acid. Plant growth-promoting rhizobacteria (PGPR) eliminate the effect of drought stress by altering root morphology, regulating the stress-responsive genes, producing phytohormones, osmolytes, siderophores, volatile organic compounds, and exopolysaccharides, and improving the 1-aminocyclopropane-1-carboxylate deaminase activities. The use of PGPR is an alternative approach to traditional breeding and biotechnology for enhancing crop productivity. Hence, that can promote drought tolerance in important agricultural crops and could be used to minimize crop losses under limited water conditions. This review deals with recent progress on the use of PGPR to eliminate the harmful effects of drought stress in traditional agriculture crops.